Back Cover: Cooperative organizations of small molecular surfactants and amphiphilic block copolymers: Roles of surfactants in the formation of binary co‐assemblies. Issue 6 (23rd December 2021) - Cao, Yuanyuan; Yang, Shaobo; Li, Yongsheng; Shi, Jianlin
Abstract : The binary co‐assembly systems consisting of amphiphilic block copolymers and surfactants have provided us a versatile platform for materials design and structural regulation. In this review (Article number 2021, e49 ), Shi, Li, and co‐workers comprehensively discussed the main three amphiphilic co‐assembly systems and their potential biological applications.